Millennial‐ to Orbital‐Scale Responses of Western Equatorial Atlantic Thermocline Depth to Changes in the Trade Wind System Since the Last Interglacial. Issue 12 (27th December 2018) - Venancio, I. M.; Mulitza, S.; Govin, A.; Santos, T. P.; Lessa, D. O.; Albuquerque, A. L. S.; Chiessi, C. M.; Tiedemann, R.; Vahlenkamp, M.; Bickert, T.; Schulz, M.
Abstract: Surface ocean circulation in the western equatorial Atlantic is mainly wind driven and plays a major role for the transport of warm waters to the North Atlantic. Past changes in the strength and direction of the trade winds are well documented, but the response of the western equatorial Atlantic circulation and water column structure to these changes is unclear. Here we used the difference between the stable isotopic oxygen composition of two species of planktonic foraminifera ( Globigerinoides ruber white and Neogloboquadrina dutertrei ) from two sediment cores collected off northeastern Brazil to investigate millennial‐ and orbital‐scale changes in upper ocean stratification since the Last Interglacial. Our records indicate enhanced upper ocean stratification during several Heinrich stadials, partly due to a shoaling of the thermocline, which was linked to a decrease in the strength of southeast trades winds. In addition, we show that a decrease in wind zonality induced by increases in Northern Hemisphere low‐latitude summer insolation causes a shoaling of the thermocline in the western equatorial Atlantic. These ocean‐atmosphere changes contributed to a reduction in the cross‐equatorial transport of warm waters, particularly during Heinrich stadials and Marine Isotope Stage 4. Key Points: Changes in western equatorial Atlantic thermocline depth were recorded on millennial and orbital time scales Shoaling of the thermocline during Heinrich stadials was associated with weak southeast trade winds Shoaling of the thermocline during periods of low‐latitude boreal summer insolation maxima occurred due to decreased wind zonality